Sistema web de planificación y ejecución de tareas en la clínica Cardiocentro Manta - Moreira Santos, Edwin Wellington (2019)
This degree work was developed with the purpose of planning and executing tasks individually or collaboratively through a web system for the staff of the Cardiocentro Manta clinic, with the purpose of favoring cost reduction, time in the use of resources and administration of the information, giving the possibility to interact with those responsible for each task. This was done under the use of the Extreme Programming methodology (XP) that allowed to follow an appropriate development process, starting with the Planning stage where a projection of the deliverables was made, the database was modeled and interface designs were developed in the Design stage, the system was developed in the PHP programming language in the Development stage, the Laravel Framework and the MySQL database management system, finally the unit tests were performed in the Testing stage and integration. The system was implemented in AWS (Amazon Web Services) and its correct functioning was verified in the system tests. Once the application was completed, percentage calculations were made in a comparative table between the system and without it, which resulted that the implementation helped in the assignment, execution and performance of tasks by 81.95%, so it concludes that the completion of this type of projects collaborates with the planning and execution of tasks by providing indicators for decision-making for the benefit of the institution.